Cutaneous sporotrichosis treatment with potassium iodide: a 24 year experience in São Paulo state, Brazil - Yamada, Karin (2011)
BACKGROUND: Sporotrichosis is a subacute or chronic disease caused by a dimorphic fungus, Sporothrix schenckii. The first and most traditional treatment is potassium iodide in satured solution (SSKI) used by DE BEURMANN in 1907. For its effectiveness, it is still used for cutaneous sporotrichosis. OBJECTIVE: To evaluate the treatment of cutaneous sporotrichosis with SSKI in relation to clinical cure, side effects, length of treatment and reactivation. METHODS: We conducted a retrospective analysis of medical records over a 24-year period (1981-2005). Patients of all ages who were treated in the hospital´s division of dermatology were included in the study providing that they had a positive culture of S. schenckii. Satured solution of potassium iodide (3 to 6g per day) was the treatment prescribed. For children, half of the dose was prescribed. RESULTS: The lymphocutaneous disease was prevalent, the cure rate was 94.7%, side effects were described in 5.5% of the cases, mean length of treatment was 3.5 months and possible reactivation was observed in 11.1%. CONCLUSION: SSKI is an effective drug, with many side effects, but with low frequency. Resolution was for maximum six months of treatment. SSKI has been found to be a very effective drug in this retrospective study of culture-proven cases of cutaneous and lymphocutaneous sporotrichosis. It should be used as first drug of choice especially in resource-limited settings.